2014
DOI: 10.3171/2014.7.focus14330
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic endonasal surgery for olfactory groove meningiomas: outcomes and limitations in 50 patients

Abstract: Object Recently, endoscopic endonasal surgery (EES) has been introduced in the management of skull base tumors, with constantly improving outcomes and increasing indications. The authors retrospectively reviewed the effectiveness of EES in the management of olfactory groove meningiomas. Methods Between February 2003 and December 2012, 50 patients (64% female) with olfactory groove meningiomas underwent E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
69
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 44 publications
(110 reference statements)
4
69
0
2
Order By: Relevance
“…In our patients, optic canal involvement was found in 9.8% of cases with a statistically significant association with the tumor diameter, consistent with the findings of Romani et al who observed the larger the tumor the more often the optic apparatus involvement (33). Additionally, vascular encasement, mainly the ACA, was also reported in case series in up to 50% of patients (7,21,28,33). Vascular encasement was seen in 8.2% of patients in our series.…”
Section: █ Referencessupporting
confidence: 91%
See 2 more Smart Citations
“…In our patients, optic canal involvement was found in 9.8% of cases with a statistically significant association with the tumor diameter, consistent with the findings of Romani et al who observed the larger the tumor the more often the optic apparatus involvement (33). Additionally, vascular encasement, mainly the ACA, was also reported in case series in up to 50% of patients (7,21,28,33). Vascular encasement was seen in 8.2% of patients in our series.…”
Section: █ Referencessupporting
confidence: 91%
“…The frequency of optic chiasm and optic nerve involvement in series of OGMs was found to be 6.5-45.4% (7,8,21,25,33,36). In our patients, optic canal involvement was found in 9.8% of cases with a statistically significant association with the tumor diameter, consistent with the findings of Romani et al who observed the larger the tumor the more often the optic apparatus involvement (33).…”
Section: █ Referencessupporting
confidence: 91%
See 1 more Smart Citation
“…3 Were any patients selected for a craniotomy or did the authors offer an endonasal approach to every patient with an olfactory groove meningioma? Do their data support this decision or should certain cases be selected for an EEA, whereas others might be better served by a transcranial approach?…”
Section: 4mentioning
confidence: 99%
“…One of the more controversial areas in this discussion is the resection of olfactory groove meningiomas. Koutourousiou et al 3 provide an outstanding addition to this evergrowing area of the literature with their series of 50 cases, the largest single series reported to date. However, their own data may lead other investigators to altogether different conclusions than the ones they themselves draw from the same data.…”
mentioning
confidence: 99%